A Compressive Review on High- and Low-Temperature Performance of Asphalt Modified with Nanomodifier. (7th April 2021) - Li, Limin; Yang, Lingming; Lin, Yuliang; Zhang, Xiancai
Abstract : At present, rutting and cracking have become serious issues in asphalt pavement, especially in the areas of summer heat and winter cold. Nanomodifier has been widely used in recent years due to its unique properties in improving the characteristics of asphalt binders. To make better use of nanomodifier to solve the problem of rutting and cracking of pavement, a compressive review on the high- and low-temperature performance of nanomodified asphalt is performed. The results indicate that for high- and low-temperature performance of asphalt binder, the effectiveness of nanomodification is found to be strictly influenced by the combination of original asphalt type, nanomodifier type, nanomodifier dosage, nanoparticle size, and preparation of nanomodified asphalt, and the high-temperature antirutting performance and low-temperature crack resistance of final blends are various with the combination. Chemical composition, microstructure, dispersion, and compatibility of final blends were the possible reason causing the difference. The rational selection of the combination can improve the high-temperature rutting resistance and the low-temperature cracking resistance of asphalt binder. So far, there is a lack of systematic investigation in this regard. Therefore, it is very necessary to study systematically the original asphalt, nanomodifier, nanomodifier dosage, nanoparticle size, and preparation of nanomodified asphalt effect on the high and low performance of nanomodified asphalt, especially in the modification mechanism in the future.